Conductive film transfer material with carrier film and method for manufacturing conductive film transfer material with carrier film

JP7608181B2Active Publication Date: 2025-01-06NITTO DENKO CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021003849
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-14
Publication Date
2025-01-06
Estimated Expiration
2041-01-14

AI Technical Summary

Benefits of technology

【0015】 本発明のキャリアフィルム付き導電性フィルム転写材は、キャリアフィルムと、仮支持体と、硬化樹脂層と、導電層とを厚み方向一方側に向かって順に備える。仮支持体と硬化樹脂層とは剥離可能である。そのため、耐屈曲性に優れる導電性フィルムを製造できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608181000002
    Figure 0007608181000002
  • Figure 0007608181000003
    Figure 0007608181000003
  • Figure 0007608181000001
    Figure 0007608181000001
Patent Text Reader

Abstract

To provide a conductive film transfer material with a carrier film that is suitable for producing a conductive film having high bending resistance and workability, and a method for producing the same.SOLUTION: A conductive film transfer material 1 with a carrier film includes a carrier film 20, a temporary support 2, a curable resin layer 3 and a conductive layer 4 in this order toward one side in a thickness direction. The temporary support 2 can be peeled off from the curable resin layer 3. The peeling force between the temporary support 2 and the curable resin layer 3 is smaller than the peeling force between the carrier film 20 and the temporary support 2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive film transfer material with a carrier film and a method for manufacturing the conductive film transfer material with a carrier film. More specifically, the present invention relates to a conductive film transfer material with a carrier film and a method for manufacturing the conductive film transfer material with a carrier film. [Background technology]

[0002] A conductive film having a conductive layer made of indium tin oxide (ITO) is known. The conductive layer is formed into a desired electrode pattern. The conductive film is used in optical products such as touch panels.

[0003] Such a conductive film can be obtained by forming a conductive layer on the surface of a substrate by a sputtering method while transporting the substrate. In such a case, a carrier film is provided on the substrate in order to ensure mechanical strength and improve transportability.

[0004] For example, a transparent conductive film laminate including a carrier film and a transparent conductive film has been proposed (see, for example, Patent Document 1). The transparent conductive film includes a transparent substrate, a cured resin layer, and a transparent conductive layer.

[0005] When a product is manufactured using the transparent conductive film, the carrier film is peeled off from the transparent substrate, and the carrier film is removed from the transparent conductive film laminate. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2020-108941 A Summary of the Invention [Problem to be solved by the invention]

[0007] In recent years, transparent conductive films are required to have bending resistance in order to be compatible with flexible displays (foldable, bendable, rollable displays, etc.).

[0008] In Patent Document 1, the carrier film is peeled off from the transparent substrate, and the carrier film is removed from the transparent conductive film laminate, so the transparent substrate remains on the transparent conductive film, which makes it difficult to make the transparent conductive film thinner and reduces bending resistance.

[0009] The present invention provides a conductive film transfer material with a carrier film, which is suitable for producing a conductive film having excellent flex resistance and workability, and a method for producing the same. [Means for solving the problem]

[0010] The present invention [1] is a conductive film transfer material with a carrier film, which comprises, in order toward one side in a thickness direction, a carrier film, a temporary support, a cured resin layer, and a conductive layer, wherein the temporary support and the cured resin layer are peelable, and the peel force between the temporary support and the cured resin layer is smaller than the peel force between the carrier film and the temporary support.

[0011] The present invention [2] includes the conductive film transfer material with a carrier film according to the above [1], in which the peel strength between the temporary support and the cured resin layer is 1.0 N / 24 mm or less.

[0012] The present invention [3] includes the conductive film transfer material with a carrier film according to the above [1] or [2], in which the amount of warping measured by the following test is -10 mm or more and 10 mm or less. Test: (1) The conductive film transfer material with carrier film is cut into a square of 100 mm x 100 mm. (2) The cut conductive film transfer material with carrier film is heated at 140°C for 90 minutes. (3) The cut conductive film transfer material with carrier film is placed on a horizontal table with the conductive layer facing up, and the vertical height from the horizontal table is measured at each of the four corners to determine the amount of warping. (4) The obtained amounts of warping are added up, and the average is calculated to determine the amount of positive warping. (5) If the amount of positive warping is 0 mm or less, the cut conductive film transfer material with carrier film is placed on a horizontal table with the carrier film facing up, and the vertical height from the horizontal table is measured at each of the four corners to determine the amount of warping. (6) The obtained amounts of warping are added up, and the average is calculated to determine the amount of negative warping.

[0013] The present invention [4] includes a method for producing a conductive film transfer material with a carrier film described in any one of the above [1] to [3], comprising a preparation step of preparing a temporary support, a cured resin layer arrangement step of arranging a cured resin layer on one surface in the thickness direction of the temporary support, a film formation step of forming a conductive layer on one surface in the thickness direction of the cured resin layer, and a carrier film arrangement step of arranging a carrier film on the other surface in the thickness direction of the temporary support.

[0014] The present invention [5] includes the method for producing a conductive film transfer material with a carrier film described above in [4], in which a carrier film arrangement step is carried out after the film formation step. Effect of the Invention

[0015] The conductive film transfer material with a carrier film of the present invention includes a carrier film, a temporary support, a cured resin layer, and a conductive layer in this order toward one side in the thickness direction. The temporary support and the cured resin layer are peelable. Therefore, a conductive film with excellent bending resistance can be produced.

[0016] Specifically, when producing a conductive film, a carrier film is provided from the viewpoint of ensuring mechanical strength and improving transportability. According to this conductive film transfer material with a carrier film, transportability can be improved by providing a carrier film on the other surface in the thickness direction of the temporary support during transport. In addition, by peeling the temporary support and the cured resin layer after transport, the carrier film can be removed together with the temporary support. In this way, a conductive film having a cured resin layer and a conductive layer without a substrate (for example, a transparent substrate) can be obtained. And, since the obtained conductive film does not have a substrate, it is thin and has excellent bending resistance.

[0017] Moreover, the peeling force between the temporary support and the cured resin layer is smaller than the peeling force between the carrier film and the temporary support. Therefore, when peeling the temporary support and the cured resin layer, peeling between the carrier film and the temporary support can be suppressed. As a result, when peeling the temporary support and the cured resin layer, the carrier film can be removed together with the temporary support. As a result, the workability is excellent.

[0018] According to the method for producing a conductive film transfer material with a carrier film of the present invention, the conductive film transfer material with a carrier film of the present invention can be suitably produced. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 shows a cross-sectional view of one embodiment of the conductive film transfer material with a carrier film of the present invention. [Diagram 2] Fig. 2 shows one embodiment of the method for producing a conductive film transfer material with a carrier film of the present invention. Fig. 2A shows a preparation step of preparing a temporary support. Fig. 2B shows a cured resin layer arrangement step of arranging a cured resin layer (hard coat layer) on one surface in the thickness direction of the temporary support. Fig. 2C shows a film formation step of forming a conductive layer on one surface in the thickness direction of the cured resin layer. Fig. 2D shows a carrier film arrangement step of arranging a carrier film on the other surface in the thickness direction of the temporary support. Fig. 2E shows a step of peeling off the carrier film from the conductive film transfer material with a carrier film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] One embodiment of the conductive film transfer material with a carrier film of the present invention will be described with reference to FIG.

[0021] In Fig. 1, the up-down direction of the paper is the up-down direction (thickness direction), the upper side of the paper is the upper side (one side in the thickness direction), and the lower side of the paper is the lower side (the other side in the thickness direction). The left-right direction and the depth direction of the paper are surface directions perpendicular to the up-down direction. Specifically, they follow the directional arrows in each figure.

[0022] <Conductive film transfer material with carrier film> The conductive film transfer material 1 with a carrier film has a film shape (including a sheet shape) with a predetermined thickness, extends in a plane direction perpendicular to the thickness direction, and has a flat upper surface and a flat lower surface.

[0023] 1, the conductive film transfer material 1 with a carrier film includes a carrier film 20, a temporary support 2, and a conductive film 10, which are arranged in this order toward one side in the thickness direction. More specifically, the conductive film transfer material 1 with a carrier film includes a carrier film 20, a temporary support 2 arranged on the upper surface (one surface in the thickness direction) of the carrier film 20, and a conductive film 10 arranged on the upper surface (one surface in the thickness direction) of the temporary support 2. Preferably, the conductive film transfer material 1 with a carrier film includes only the carrier film 20, the temporary support 2, and the conductive film 10.

[0024] As will be described in detail later, the conductive film 10 does not include a transparent substrate, and includes a cured resin layer 3 and a conductive layer 4 in this order toward one side in the thickness direction. Therefore, more specifically, the conductive film transfer material 1 with a carrier film includes a carrier film 20, a temporary support 2, a cured resin layer 3, and a conductive layer 4 in this order toward one side in the thickness direction.

[0025] The thickness of the conductive film transfer material 1 with a carrier film is, for example, 300 μm or less, preferably 150 μm or less, and more preferably 100 μm or less.

[0026] <Carrier film> The carrier film 20 is a protective member that is provided during the production of the conductive film 10 in order to ensure mechanical strength and improve transportability.

[0027] The carrier film 20 includes a protective base material 21 and an adhesive layer 22 in this order toward one side in the thickness direction. More specifically, the carrier film 20 includes a protective base material 21 and an adhesive layer 22 disposed on an upper surface (one surface in the thickness direction) of the protective base material 21. Preferably, the carrier film 20 includes the protective base material 21 and the adhesive layer 22.

[0028] The protective substrate 21 is a supporting substrate for ensuring the mechanical strength of the carrier film 20 .

[0029] The protective substrate 21 has a film shape.

[0030] The protective substrate 21 may be, for example, a polymer film.

[0031] Examples of materials for the polymer film include polyester resin, (meth)acrylic resin, olefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, cellulose resin, and polystyrene resin. Examples of polyester resin include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of (meth)acrylic resin include polymethyl methacrylate. Examples of olefin resin include polyethylene, polypropylene, and cycloolefin polymer. Examples of cellulose resin include triacetyl cellulose.

[0032] The material of the polymer film is preferably a polyester resin, more preferably polyethylene terephthalate.

[0033] The thickness of the protective substrate 21 is, for example, 1 μm or more, preferably 5 μm or more, more preferably 10 μm or more, and for example, 200 μm or less, preferably 150 μm or less, more preferably 100 μm or less.

[0034] The thickness of the protective substrate 21 can be measured using a dial gauge (manufactured by PEACOCK, "DG-205").

[0035] The pressure-sensitive adhesive layer 22 is a layer (pressure-sensitive adhesive layer) for attaching the carrier film 20 (protective substrate 21) to the temporary support 2. In addition, after attachment, the pressure-sensitive adhesive layer 22 is a layer (easy-peel layer) that can be and is easily peeled off from the temporary support 2.

[0036] The pressure-sensitive adhesive layer 22 has a film shape.

[0037] The pressure-sensitive adhesive layer 22 is formed from a pressure-sensitive adhesive composition.

[0038] Examples of the adhesive composition include an acrylic adhesive composition, a rubber adhesive composition, a silicone adhesive composition, a polyester adhesive composition, a polyurethane adhesive composition, a polyamide adhesive composition, an epoxy adhesive composition, a vinyl alkyl ether adhesive composition, and a fluorine-based adhesive composition. These adhesive compositions can be used alone or in combination of two or more kinds.

[0039] As the pressure-sensitive adhesive composition, from the viewpoints of adhesiveness and peelability, preferably, an acrylic pressure-sensitive adhesive composition is used.

[0040] The acrylic pressure-sensitive adhesive composition contains, for example, an acrylic polymer obtained by polymerizing a monomer component containing an alkyl (meth)acrylate ester as a polymer component.

[0041] The (meth)acrylic acid alkyl ester is an acrylic acid alkyl ester and / or a methacrylic acid alkyl ester. Examples of the (meth)acrylic acid alkyl ester include linear or branched (meth)acrylic acid alkyl esters having an alkyl moiety with 4 to 14 carbon atoms. Examples of the (meth)acrylic acid alkyl esters having linear or branched alkyl moieties with 4 to 14 carbon atoms include butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, neopentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, and tetradecyl (meth)acrylate. The (meth)acrylic acid alkyl esters can be used alone or in combination of two or more kinds. As the (meth)acrylic acid alkyl ester, preferably, butyl (meth)acrylate is used, and more preferably, butyl acrylate is used.

[0042] The mixing ratio of the (meth)acrylic acid alkyl ester relative to 100 parts by mass of the total amount of the monomer components is, for example, 80 parts by mass or more, preferably 85 parts by mass or more, and for example, 99 parts by mass or less, preferably 95 parts by mass or less.

[0043] The monomer component may contain a functional group-containing monomer in addition to the (meth)acrylic acid alkyl ester.

[0044] Examples of functional group-containing monomers include carboxyl group-containing monomers and hydroxyl group-containing monomers. Examples of carboxyl group-containing monomers include acrylic acid and methacrylic acid. Examples of hydroxyl group-containing monomers include 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate. The functional group-containing monomers can be used alone or in combination of two or more.

[0045] As the functional group-containing monomer, preferably, a carboxyl group-containing monomer is used, and more preferably, acrylic acid is used.

[0046] The mixing ratio of the functional group-containing monomer relative to 100 parts by mass of the total amount of the monomer components is, for example, 1 part by mass or more, for example, 5 parts by mass or more, and 20 parts by mass or less, preferably 15 parts by mass or less.

[0047] The acrylic pressure-sensitive adhesive composition can be obtained, for example, by solution polymerization, bulk polymerization, or photopolymerization.

[0048] The pressure-sensitive adhesive composition preferably contains a crosslinking agent. Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based resins, aziridine derivatives, and metal chelate compounds, and preferably epoxy-based crosslinking agents. The crosslinking agents can be used alone or in combination of two or more.

[0049] The mixing ratio of the crosslinking agent is, relative to 100 parts by mass of the polymer component, for example, 1 part by mass or more, preferably 4 parts by mass or more, and for example, 15 parts by mass or less, preferably 10 parts by mass or less. By adjusting the mixing ratio of the crosslinking agent, the peel strength of the pressure-sensitive adhesive layer 22 can be adjusted.

[0050] The pressure-sensitive adhesive composition may further contain a tackifier resin, a processing aid, a pigment, a flame retardant, a filler, a softener, and an anti-aging agent as appropriate.

[0051] The pressure-sensitive adhesive layer 22 has a thickness of, for example, 1 μm or more, preferably 5 μm or more, and for example, 50 μm or less, preferably 30 μm or less.

[0052] To prepare the carrier film 20, the pressure-sensitive adhesive layer 22 is disposed on one surface of the protective substrate 21 in the thickness direction.

[0053] To dispose the adhesive layer 22 on one surface in the thickness direction of the protective substrate 21, an adhesive composition is applied to one surface in the thickness direction of the protective substrate 21, and if necessary, heated and dried. In this way, the adhesive layer 22 is disposed on one surface in the thickness direction of the protective substrate 21.

[0054] In addition, when the pressure-sensitive adhesive composition contains a crosslinking agent, a crosslinking reaction proceeds simultaneously with the drying or by subsequent aging. The aging conditions are appropriately set depending on the type of crosslinking agent. The aging temperature is, for example, 20° C. or higher and, for example, 160° C. or lower. The aging time is, for example, 1 minute or higher and, for example, 7 days or shorter.

[0055] In addition, before or after aging, a release film (not shown) may be laminated on one surface in the thickness direction of the pressure-sensitive adhesive layer 22. As the release film, for example, polyethylene terephthalate can be used.

[0056] In this way, the carrier film 20 is prepared.

[0057] <Temporary support> The temporary support 2 has a film shape. The temporary support 2 is disposed on the entire lower surface of the conductive film 10 (cured resin layer 3) so as to be in contact with the lower surface of the conductive film 10 (cured resin layer 3).

[0058] The temporary support 2 is peelable from the cured resin layer 3 .

[0059] As described in detail below, this allows the carrier film 20 to be peeled off together with the temporary support 2.

[0060] More specifically, the peeling force between the temporary support 2 and the cured resin layer 3 is smaller than the peeling force between the carrier film 20 and the temporary support 2 .

[0061] Therefore, when peeling the temporary support 2 from the cured resin layer 3, peeling between the carrier film 20 and the temporary support 2 can be suppressed. As a result, when the temporary support 2 and the cured resin layer 3 are peeled off, the carrier film 20 can be removed together with the temporary support 2. As a result, workability is excellent.

[0062] On the other hand, if the peeling force between the temporary support 2 and the cured resin layer 3 is greater than the peeling force between the carrier film 20 and the temporary support 2, the carrier film 20 and the temporary support 2 will peel off before the temporary support 2 and the cured resin layer 3 peel off. In this case, the temporary support 2 cannot be removed together with the carrier film 20 (in other words, the temporary support 2 and the carrier film 20 cannot be peeled off at the same time). As a result, workability is reduced.

[0063] Specifically, the peeling force between the temporary support 2 and the cured resin layer 3 is, for example, 1.0 N / 24 mm or less, preferably 0.5 N / 24 mm or less, and for example, 0.01 N / 24 mm or more.

[0064] The peeling force between the carrier film 20 and the temporary support 2 is, for example, 1.5 N / 24 mm or less, preferably 1.0 N / 24 mm or less, and for example, 0.02 N / 24 mm or more.

[0065] The difference between the peel strength of the carrier film 20 and the temporary support and the peel strength of the temporary support 2 and the cured resin layer 3 (the peel strength of the carrier film 20 and the temporary support - the peel strength of the temporary support 2 and the cured resin layer 3) is, for example, 0.01 N / 24 mm or more, preferably 0.2 N / 24 mm or more, and for example, 1.5 N / 24 mm or less, preferably 1.0 N / 24 mm or less, and more preferably 0.5 N / 24 mm or less.

[0066] If the peel strength is equal to or less than the above upper limit, the temporary support 2 and the cured resin layer 3 can be easily peeled off.

[0067] The peel strength can be measured by the peel test described in the Examples below.

[0068] The temporary support 2 may be, for example, a flexible plastic film. Examples of materials for the flexible plastic film include olefin resins and polyester resins. Examples of olefin resins include polyethylene, polypropylene, and cycloolefin polymers. Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate.

[0069] The temporary support 2 has a thickness of, for example, 3 μm or more, preferably 10 μm or more, and for example, 200 μm or less, preferably 100 μm or less, more preferably 50 μm or less.

[0070] In order to adjust the peel strength to the above range, the temporary support 2 is preferably subjected to a release treatment. Examples of the release treatment include a release treatment using a silicone-based, fluorine-based, long-chain alkyl-based, or fatty acid amide-based release agent, or a release treatment using silica powder.

[0071] <Conductive film> The conductive film 10 includes a cured resin layer 3 and a conductive layer 4 in this order toward one side in the thickness direction. More specifically, the conductive film 10 includes a cured resin layer 3 and a conductive layer 4 disposed on the upper surface (one surface in the thickness direction) of the cured resin layer 3. Preferably, the conductive film 10 includes only the cured resin layer 3 and the conductive layer 4. The conductive film 10 is, for example, a part of a touch panel substrate or an electromagnetic shield provided in an image display device, that is, it is not an image display device. In other words, the conductive film 10 is a part for producing an image display device or the like, does not include an image display element such as an OLED module, is distributed as a part alone, and is an industrially applicable device.

[0072] <Cured resin layer> The cured resin layer 3 has a film shape. The cured resin layer 3 is disposed on the entire lower surface of the conductive layer 4 so as to be in contact with the lower surface of the conductive layer 4.

[0073] The cured resin layer 3 may be a hard coat layer.

[0074] In the following description, the cured resin layer 3 is a hard coat layer.

[0075] The hard coat layer is a protective layer for preventing the conductive layer 4 from being scratched.

[0076] The hard coat layer is formed, for example, from a hard coat composition.

[0077] The hard coat composition comprises a resin and, optionally, particles, i.e., the hard coat layer comprises a resin and, optionally, particles.

[0078] Examples of the resin include thermoplastic resins and curable resins. Examples of the thermoplastic resin include polyolefin resins.

[0079] Examples of the curable resin include active energy ray curable resins that are cured by irradiation with active energy rays (e.g., ultraviolet rays and electron beams) and thermosetting resins that are cured by heating. Examples of the curable resin include active energy ray curable resins.

[0080] Examples of the active energy ray curable resin include (meth)acrylic ultraviolet ray curable resin, urethane resin, melamine resin, alkyd resin, siloxane polymer, and organic silane condensate. Examples of the active energy ray curable resin include (meth)acrylic ultraviolet ray curable resin.

[0081] The resin may contain, for example, a reactive diluent as described in JP-A-2008-88309. Specifically, the resin may contain a polyfunctional (meth)acrylate.

[0082] The resins can be used alone or in combination of two or more kinds.

[0083] Examples of the particles include metal oxide particles and organic particles. Examples of materials for the metal oxide particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. Examples of materials for the organic particles include polymethyl methacrylate, silicone, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate.

[0084] The particles can be used alone or in combination of two or more kinds.

[0085] By adjusting the particle blending ratio and / or the average particle size of the particles to a predetermined ratio, the arithmetic mean roughness Ra of the conductive layer 4, which will be described later, can be adjusted to fall within a predetermined range, which will be described later.

[0086] Specifically, the mixing ratio of the particles is, for example, 1 part by mass or more, preferably 3 parts by mass or more, and for example, 10 parts by mass or more, and for example, 20 parts by mass or less, relative to 100 parts by mass of the resin.

[0087] When the blending ratio of the particles is equal to or less than the above upper limit, the arithmetic mean roughness Ra of the conductive layer 4, which will be described later, can be adjusted to fall within a predetermined range, which will be described later.

[0088] The average particle size of the particles is, for example, 10 μm or less, preferably 8 μm or less, and, for example, 1 nm or more. When nanoparticles are used as the particles, the average particle size of the particles is, for example, 100 nm or less, preferably 70 nm or less, and, for example, 1 nm or more. The average particle size of the particles is determined, for example, as the D50 value (cumulative 50% median size) based on the particle size distribution determined by a particle size distribution measurement method in a laser scattering method.

[0089] When the average particle size of the particles is within the above range, the arithmetic mean roughness Ra of the conductive layer 4, which will be described later, can be adjusted to a predetermined range, which will be described later.

[0090] In addition, the hard coat composition may contain a thixotropy imparting agent, a photopolymerization initiator, a filler (e.g., organic clay), and a leveling agent in an appropriate ratio, if necessary. In addition, the hard coat composition may be diluted with a known solvent.

[0091] To form a hard coat layer, a diluted solution of the hard coat composition is applied to one surface in the thickness direction of the temporary support 2, and dried by heating as necessary, as described in detail below. After drying, the hard coat composition is cured, for example, by irradiation with active energy rays.

[0092] In this way, a hard coat layer is formed.

[0093] The thickness of the hard coat layer is, for example, 1 μm or more and 7 μm or less, preferably 3 μm or less, more preferably 2.5 μm or less, and even more preferably 1.5 μm or less.

[0094] The thickness of the hard coat layer can be measured, for example, by observing a cross section using a transmission electron microscope.

[0095] <Conductive layer> The conductive layer 4 is amorphous or crystalline. In addition, the conductive layer 4 is preferably a transparent layer (transparent conductive layer) that exhibits excellent conductivity.

[0096] The conductive layer 4 has a film shape. The conductive layer 4 is disposed on the entire upper surface of the cured resin layer 3 so as to be in contact with the upper surface of the cured resin layer 3.

[0097] Examples of materials for the conductive layer 4 include metal oxides. The metal oxides include at least one metal element selected from the group consisting of In, Sn, Zn, Ga, Sb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, and W. The metal oxides may be doped with a metal element in the above group, if necessary.

[0098] Examples of the conductive layer 4 include indium-containing oxides and antimony-containing oxides. Examples of the indium-containing oxides include indium tin composite oxide (ITO). Examples of the antimony-containing oxides include antimony tin composite oxide (ATO). From the viewpoint of low resistance, the conductive layer 4 is preferably an indium-containing oxide, more preferably ITO.

[0099] When ITO is used as the material of the conductive layer 4, the tin oxide (SnO2) content is, for example, 0.5 mass% or more, preferably 3 mass% or more, more preferably 5 mass% or more, and for example, 15 mass% or less, preferably 13 mass% or less, based on the total amount of tin oxide and indium oxide (In2O3). If the tin oxide content is equal to or more than the above lower limit, the durability of the ITO layer can be further improved. If the tin oxide content is equal to or less than the above upper limit, the crystallization of the ITO layer can be facilitated, and the stability of the transparency and resistivity can be improved.

[0100] In this specification, "ITO" refers to a composite oxide containing at least indium (In) and tin (Sn), and may contain additional components other than these. Examples of additional components include metal elements other than In and Sn. Specific examples of such metal elements include Zn, Ga, Sb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, W, Fe, Pb, Ni, Nb, Cr, and Ga.

[0101] The conductive layer 4 is preferably crystalline.

[0102] If the conductive layer 4 is crystalline, the surface resistivity, which will be described later, can be reduced.

[0103] The crystallinity of conductive layer 4 can be determined, for example, by immersing conductive film 10 in hydrochloric acid (20°C, concentration 5% by mass) for 15 minutes, followed by rinsing with water and drying, and then measuring the inter-terminal resistance over a distance of about 15 mm from the surface on the conductive layer 4 side. If the inter-terminal resistance over 15 mm of conductive film 10 after the above immersion, rinsing with water, and drying is 10 kΩ or less, conductive layer 4 is crystalline. On the other hand, if the resistance exceeds 10 kΩ, conductive layer 4 is amorphous.

[0104] The resistivity of the upper surface of the conductive layer 4 is, for example, 20×10 -4 Ω cm or less, preferably 8.0×10 -4 Ω cm or less, e.g., 0.1×10 -4 The resistivity is Ω·cm or more. The resistivity can be measured by the four-terminal method in accordance with JIS K7194 (1994).

[0105] The surface resistivity of the upper surface of the conductive layer 4 is, for example, 150 Ω / □ or less, preferably 50 Ω / □ or less, and for example, 0.1 Ω / □ or more. The surface resistivity can be measured by a four-terminal method in accordance with JIS K7194 (1994).

[0106] If the surface resistivity is equal to or less than the above upper limit, the conductive film 10 can be used, for example, in a large touch panel.

[0107] The conductive layer 4 has an arithmetic mean roughness Ra (specifically, the arithmetic mean roughness Ra of one surface in the thickness direction of the conductive layer 4) of, for example, 7.0 nm or less, preferably 1.5 nm or less, and for example, 0.2 nm or more.

[0108] The conductive layer 4 is determined, for example, from an observation image of 1 μm square using an AFM (atomic force microscope) in accordance with JIS B0681-6 (2017).

[0109] The thickness of the conductive layer 4 is, for example, 10 nm or more, preferably 30 nm or more, and for example, 150 nThe thickness of the conductive layer 4 can be measured by observing a cross section of the conductive film 10 using, for example, a transmission electron microscope.

[0110] The conductive layer 4 has a total light transmittance (JIS K 7375-2008) of, for example, 50% or more, or preferably 60% or more.

[0111] <Method of manufacturing conductive film transfer material with carrier film> The manufacturing method of the conductive film transfer material 1 with a carrier film includes a preparation process of preparing a temporary support 2, a cured resin layer arrangement process of arranging a cured resin layer 3 (hard coat layer) on one surface in the thickness direction of the temporary support 2, a film formation process of forming a conductive layer 4 on one surface in the thickness direction of the cured resin layer 3, and a carrier film arrangement process of arranging a carrier film 20 on the other surface in the thickness direction of the temporary support 2.

[0112] In this manufacturing method, a carrier film disposing step is preferably carried out after the film forming step.

[0113] If the carrier film placement process is carried out after the film formation process, the carrier film 20 is not placed during the film formation process, so that impurity gas originating from the carrier film 20 can be prevented from impeding the formation of the conductive layer 4.

[0114] In the preparation step, a temporary support 2 is prepared as shown in FIG. 2A.

[0115] In the cured resin layer disposing step, a cured resin layer 3 (hard coat layer) is disposed on one surface of the temporary support 2 in the thickness direction, as shown in FIG. 2B.

[0116] To dispose a cured resin layer 3 (hard coat layer) on one surface in the thickness direction of the temporary support 2, first, a surface treatment is performed on the surface of the temporary support 2 (the surface that has been subjected to the above-mentioned release treatment, or the surface that has not been subjected to the above-mentioned release treatment).

[0117] Examples of the surface treatment include corona treatment, plasma treatment, flame treatment, ozone treatment, primer treatment, glow treatment, and saponification treatment. The surface treatment is preferably plasma treatment.

[0118] Next, a diluted solution of the hard coat composition is applied to one surface in the thickness direction of the temporary support 2, and after drying, the hard coat composition is cured by ultraviolet light irradiation or heating. This forms a cured resin layer 3 (hard coat layer) on one surface in the thickness direction of the temporary support 2. This results in a transfer sheet 30 having the temporary support 2 and the cured resin layer 3 in this order toward one side in the thickness direction.

[0119] In the film-forming step, as shown in FIG. 2C, a conductive layer 4 is formed on one surface in the thickness direction of the cured resin layer 3.

[0120] To form the conductive layer 4 on one side in the thickness direction of the cured resin layer 3, first, the transfer sheet 30 is wound around a delivery roll (not shown).

[0121] Next, the conveying sheet 30 is sent out from the send-out rolls. Then, while the conveying sheet 30 is conveyed downstream in the conveying direction, the conductive layer 4 is formed on one surface in the thickness direction of the cured resin layer 3 by a sputtering method.

[0122] The conveying speed is, for example, 1 m / min or more, preferably 2 m / min or more, and for example, 10 m / min or less, preferably 7 m / min or less.

[0123] In the sputtering method, a target (material of the conductive layer 4) and the cured resin layer 3 are placed facing each other in a vacuum chamber. Next, gas is supplied and a voltage is applied from a power source. This accelerates gas ions and irradiates the target, sputtering the target material from the target surface. The target material is then deposited on one side of the cured resin layer 3 in the thickness direction.

[0124] The gas may be, for example, an inert gas. The inert gas may be, for example, argon gas. If necessary, a reactive gas (for example, oxygen gas) may be used in combination. When a reactive gas is used in combination, the flow rate ratio (sccm) of the reactive gas is not particularly limited. Specifically, the flow rate ratio of the reactive gas is, for example, 0.1 flow rate % or more and 100 flow rate % or less with respect to the total flow rate ratio of the sputtering gas and the reactive gas.

[0125] The pressure during sputtering is, for example, 0.1 Pa or more and, for example, 1.0 Pa or less, preferably 0.7 Pa or less.

[0126] The power source may be, for example, a DC power source, an AC power source, an MF power source, or an RF power source, or may be a combination of these.

[0127] The discharge output is, for example, 10 kW or more, preferably 20 kW or more, and for example, 305 kW or less.

[0128] Thereby, the conductive layer 4 is disposed on one surface of the cured resin layer 3 in the thickness direction.

[0129] 2D, in the carrier film disposing step, the carrier film 20 is disposed on the other side in the thickness direction of the temporary support 2. To dispose the carrier film 20 on the other side in the thickness direction of the temporary support 2, first, the carrier film 20 is prepared by the method described above.

[0130] Next, the carrier film 20 is placed on the other side in the thickness direction of the temporary support 2 with the pressure-sensitive adhesive layer 22 of the carrier film 20 interposed therebetween.

[0131] Thereafter, from the viewpoint of improving crystallinity, the formed conductive layer 4 can be heated. The heating temperature is, for example, not less than 80° C. and not more than 160° C. The heating time is, for example, not less than 10 minutes and not more than 120 minutes.

[0132] As a result of the above, a conductive film transfer material 1 with a carrier film is obtained, which is provided with the carrier film 20, the temporary support 2, the cured resin layer 3, and the conductive layer 4 in this order toward one side in the thickness direction.

[0133] The amount of warping of the conductive film transfer material 1 with carrier film, measured by the following test, is, for example, -10 mm or more, preferably -5 mm or more, more preferably -3 mm or more, and for example, 10 mm or less, preferably 5 mm or less, more preferably 3 mm or less, and even more preferably 2 mm or less.

[0134] In the test, first, the conductive film transfer material 1 with the carrier film is cut into a square of 100 mm x 100 mm. The cut conductive film transfer material 1 with the carrier film is heated at 140 ° C for 90 minutes. Next, the cut conductive film transfer material 1 with the carrier film is placed on a horizontal table with the conductive layer 4 facing up, and the vertical height from the horizontal table is measured at each of the four corners to determine the amount of warping. The obtained amounts of warping are summed up, and the average value is calculated to determine the amount of positive warping. If the amount of positive warping is 0 mm or less, the cut conductive film transfer material 1 with the carrier film is placed on a horizontal table with the carrier film 20 facing up, and the vertical height from the horizontal table is measured at each of the four corners to determine the amount of warping. The obtained amounts of warping are summed up, and the average value is calculated to determine the amount of negative warping.

[0135] When the amount of warping is within the above range, the transportability is excellent.

[0136] When a product is manufactured using the conductive film 10, the carrier film 20 is peeled off from the conductive film transfer material 1 with the carrier film, as shown in Fig. 2E. Specifically, the temporary support 2 and the cured resin layer 3 are peeled off, and the carrier film 20 is peeled off together with the temporary support 2.

[0137] As a result, a conductive film 10 is obtained which includes the cured resin layer 3 and the conductive layer 4 in this order towards one side in the thickness direction.

[0138] The conductive layer 4 can also be patterned before or after peeling off the carrier film 20. The patterning is performed, for example, by etching.

[0139] <Action and effect> The conductive film transfer material 1 with a carrier film includes a carrier film 20, a temporary support 2, a cured resin layer 3 (hard coat layer), and a conductive layer 4 in this order toward one side in the thickness direction. The temporary support 2 and the cured resin layer 3 (hard coat layer) are peelable. Therefore, a conductive film 10 with excellent bending resistance can be produced.

[0140] Specifically, when the conductive film 10 is manufactured, the carrier film 20 is provided from the viewpoint of ensuring mechanical strength and improving transportability. According to this conductive film transfer material 1 with a carrier film, transportability can be improved by providing the carrier film 20 on the other surface in the thickness direction of the temporary support 2 during transport. Furthermore, by peeling the temporary support 2 and the cured resin layer 3 after transport, the carrier film 20 can be removed together with the temporary support 2. In this way, a conductive film 10 that does not include a substrate (for example, a transparent substrate) and includes the cured resin layer 3 and the conductive layer 4 can be obtained. Since the obtained conductive film 10 does not include a substrate, it is thin and has excellent bending resistance.

[0141] Furthermore, the peeling force between the temporary support 2 and the cured resin layer 3 is smaller than the peeling force between the carrier film 20 and the temporary support 2. Therefore, when peeling the temporary support 2 and the cured resin layer 3, peeling between the carrier film 20 and the temporary support 2 can be suppressed. As a result, when the temporary support 2 and the cured resin layer 3 are peeled off, the carrier film 20 can be removed together with the temporary support 2. As a result, workability is excellent.

[0142] According to this method for producing the conductive film transfer material 20 with a carrier film, the conductive film transfer material 1 with a carrier film can be suitably produced.

[0143] <Modification> In the modified example, the same components and steps as those in the first embodiment are denoted by the same reference numerals, and detailed description thereof will be omitted. In addition, the modified example can achieve the same effects as those in the first embodiment, unless otherwise specified. Furthermore, the first embodiment and its modified example can be appropriately combined.

[0144] In the above description, the cured resin layer 3 is a hard coat layer, but the cured resin layer 3 may be an optical adjustment layer.

[0145] The optical adjustment layer is a layer that adjusts the optical properties (e.g., refractive index) of the conductive film 10 in order to suppress visibility of the pattern of the conductive layer 4 and suppress reflection at interfaces within the conductive film 10 while ensuring excellent transparency in the conductive film 10.

[0146] Furthermore, as the cured resin layer 3, a hard coat layer and an optical adjustment layer can be used in combination (multilayer including a hard coat layer and an optical adjustment layer). EXAMPLES

[0147] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the examples and comparative examples. The specific numerical values ​​of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".

[0148] 1. Manufacturing of conductive film transfer material with carrier film Example 1 <Preparation process> As a temporary support, a polyethylene terephthalate substrate (manufactured by PANAC Corporation, product name "Panapeel" TP series) having one side subjected to a release treatment was prepared.

[0149] <Cured resin layer placement process> A hard coat composition was prepared containing 100 parts by mass of an ultraviolet-curable resin composition (manufactured by DIC Corporation, product name "Luxidia (registered trademark) V-6000") and 3 parts by mass of a photoreaction initiator.

[0150] Then, the hard coat composition was applied to the release-treated surface of the temporary support using a gravure coater so that the thickness after drying would be 1 μm. Thereafter, the applied film was heated at 80° C. Next, a high-pressure mercury lamp was used to apply an integrated light amount of 250 mJ / cm 2 2 The hard coat composition was cured by irradiating the temporary support with ultraviolet light of 1000 nm to form a hard coat layer on one surface in the thickness direction of the temporary support, thereby obtaining a conveying sheet.

[0151] <Film forming process> A sintered target containing indium oxide and tin oxide in a mass ratio of 90:10 was attached to a parallel plate type winding magnetron sputtering device, and the partial pressure of water was reduced to 5×10 by evacuation while conveying the conveying sheet. -4 The vacuum was evacuated until the pressure reached 1 Pa. Thereafter, the introduction rates of argon gas and oxygen gas were adjusted, and while the conveying sheet was conveyed at a conveying speed of 4.0 m / min and a conveying tension of 200 to 500 N, a film was formed on one surface in the thickness direction of the hard coat layer by DC sputtering at an output of 24.2 kW. As a result, a conductive layer (ITO layer) having a thickness of 50 nm was formed on one surface in the thickness direction of the hard coat layer.

[0152] <Carrier film placement process> As a protective substrate, a PET film having a thickness of 125 μm was prepared.

[0153] Next, a pressure-sensitive adhesive composition was prepared. Specifically, an acrylic polymer was obtained by solution polymerization of a monomer component containing butyl acrylate / acrylic acid (100 / 6). 6 parts by weight of an epoxy crosslinking agent was added to 100 parts by weight of this acrylic polymer to prepare a pressure-sensitive adhesive composition.

[0154] Next, this adhesive composition was applied to one surface in the thickness direction of a PET film (protective substrate) and heated at 150° C. for 90 seconds to form an adhesive layer having a thickness of 10 μm. Next, a silicone-treated surface of a PET film (release liner) having a thickness of 25 μm that had been silicone-treated was attached to one surface in the thickness direction of this adhesive layer, and the silicone-treated surface was stored at 50° C. for 2 days. This resulted in a carrier film.

[0155] Thereafter, the PET film (release liner) was peeled off, and one thickness-wise surface of the pressure-sensitive adhesive layer was attached to the other thickness-wise surface of the temporary support, thereby obtaining a conductive film with a carrier film including a carrier film, a temporary support, a hard coat layer, and a conductive layer in that order toward one thickness-wise side.

[0156] Example 2 and Example 3 A conductive film with a carrier film was obtained in the same manner as in Example 1. However, the thickness of the hard coat layer was changed according to Table 1.

[0157] Example 4 A conductive film transfer material with a carrier film was obtained in the same manner as in Example 1. However, after the carrier film arrangement step, a heat treatment was carried out in a heated oven at 140° C. for 90 minutes to cause the conductive layer to crystallize.

[0158] Example 5 A conductive film transfer material with a carrier film was obtained in the same manner as in Example 1. However, in the cured resin layer arrangement step, a hard coat composition was used in which an ultraviolet curable resin composition (manufactured by DIC Corporation, product name "Unidic ELS888") and an ultraviolet curable resin composition (manufactured by DIC Corporation, product name "Unidic RS28-605") were mixed in a weight ratio of 8:2.

[0159] Example 6 A conductive film transfer material with a carrier film was obtained in the same manner as in Example 1. However, in the cured resin layer arrangement step, a hard coat composition was used in which an ultraviolet curable resin composition (manufactured by DIC Corporation, product name "Unidic ELS888") and an ultraviolet curable resin composition (manufactured by DIC Corporation, product name "Unidic RS28-605") were mixed in a weight ratio of 2:8. The thickness of the hard coat layer was changed according to Table 1.

[0160] Comparative Example 1 and Comparative Example 2 A conductive film with a carrier film was obtained in the same manner as in Example 1. However, the thickness of the hard coat layer was changed according to Table 1. After the carrier film arrangement step, a heat treatment was performed at 140° C. for 90 minutes in a heated oven to convert the conductive layer into a crystal.

[0161] Comparative Example 3 The preparation step, the cured resin layer disposing step, and the film forming step were carried out in the same manner as in Example 1. That is, the carrier film disposing step was not carried out in Comparative Example 3. As a result, a laminate having a temporary support, a hard coat layer, and a conductive layer 4 in this order toward one side in the thickness direction was obtained.

[0162] 2. Evaluation (peel strength) The peel strength (peel strength between the temporary support and the cured resin layer, and the peel strength between the carrier film and the temporary support) was measured by a peel test (flat cross-stage method) using a Kyowa Interface Science Co., Ltd. adhesive / film peeling analyzer VPA-2. The results are shown in Table 1. Below, the method for measuring the peel strength between the temporary support and the cured resin layer, and the method for measuring the peel strength between the carrier film and the temporary support will be described in detail.

[0163] First, the method for measuring the peel strength between the temporary support and the cured resin layer will be described in detail. First, in each example and each comparative example, a preparation step, a cured resin layer arrangement step, and a film formation step were carried out in order to prepare a first peel strength test sample having a temporary support, a temporary support, a cured resin layer, and a conductive layer in order toward one side in the thickness direction.

[0164] The peel strength between the temporary support and the cured resin layer was measured for the first peel strength test sample according to the following steps: In Examples 1 to 3, 5, and 6, the following steps B to F were performed, and in Example 4 and Comparative Examples 1 and 2, the following steps A to F were performed. Step A: First, the peel force test sample was heated in a hot air oven at 140° C. for 90 minutes. Step B: First peel force test samples were cut to 24 mm x 100 mm. Step C: A glass substrate was attached to one surface in the thickness direction of the conductive layer of the first peel strength test sample via an adhesive layer having a peel strength of 5 N / 24 mm or more. A roller was used for attachment. Step D: A 24mm x 150mm adhesive tape (Sekisui Cellotape No. 252) was attached to the other surface in the thickness direction of the temporary support of the conductive film transfer material by 24mm x 100mm. In other words, of the 24mm x 150mm adhesive tape, 24mm x 100mm was the attached portion and 24mm x 50mm was the unattached portion. A roller was used for the attachment. Step E: The sample prepared in step D was set on the stage, and the unattached portion of the adhesive tape (Sekisui Cellotape No. 252) was attached to the measurement probe. Step F: The peel force was calculated as the average value of the peel force from a movement of 20 mm to 80 mm (peel speed: 0.1 m / min, peel angle: 90°) with the unbonded portion and the bonded portion being regarded as a peel distance of 0 mm.

[0165] Next, the method for measuring the peeling force between the carrier film and the temporary support will be described in detail. First, in each example and each comparative example, the non-release treated side of a polyethylene terephthalate substrate (manufactured by PANAC Corporation, product name "Panapeel" TP series) with one side subjected to release treatment was attached to the adhesive side of the carrier film. A roller was used for bonding. In this way, a second peeling force test sample including the carrier film and the temporary support was prepared.

[0166] The peel strength between the carrier film and the temporary support was measured for the second peel strength test sample according to the following steps: In Examples 1 to 3, 5, and 6 and Comparative Example 1, the following steps H to M were performed, and in Example 4 and Comparative Example 2, the following steps G to M were performed. Step G: The second peel force test sample was heated in a hot air oven at 140° C. for 90 minutes. Step H: A second peel force test sample was cut to 24 mm x 100 mm. Step I: A glass substrate was attached to the temporary support surface of the second peel strength test sample via an adhesive layer having a peel strength of 5 N / 24 mm or more. A roller was used for attachment. Step J: A 24mm x 150mm adhesive tape (Sekisui Cellotape No. 252) was attached to the carrier film surface of the second peel strength test sample by 24mm x 100mm. In other words, of the 24mm x 150mm adhesive tape, 24mm x 100mm was the attached portion and 24mm x 50mm was the unattached portion. A roller was used for the attachment. Step K: The sample prepared in step D was set on the stage, and the unattached portion of the adhesive tape (Sekisui Cellotape No. 252) was attached to the measurement probe. Step M: The peel distance for the unbonded area and the bonded area was set to 0 mm, and the average peel force from a movement of 20 mm to 80 mm was calculated as the peel force (peel speed: 0.1 m / min, peel angle: 90°).

[0167] (peelability) The peelability was evaluated according to the following criteria, and the results are shown in Table 1. standard ◯: In the above peel strength evaluation, the peel strength between the temporary support and the cured resin layer is smaller than the peel strength between the carrier film and the temporary support. ×: In the above evaluation of peel strength, the peel strength between the temporary support and the cured resin layer is greater than the peel strength between the carrier film and the temporary support.

[0168] (Warpage) The conductive film transfer material with carrier film of each Example and Comparative Example was cut into a square of 100 mm x 100 mm. The cut conductive film transfer material with carrier film was heated at 140 ° C for 90 minutes. Next, the cut conductive film transfer material with carrier film was placed on a horizontal table with the conductive layer 4 facing up, and the vertical height from the horizontal table was measured at each of the four corners to determine the amount of warping. The obtained amounts of warping were summed up, and the average value was calculated to determine the amount of positive warping. When the amount of positive warping was 0 mm or less, the cut conductive film transfer material with carrier film was placed on a horizontal table with the carrier film facing up, and the vertical height from the horizontal table was measured at each of the four corners to determine the amount of warping. The obtained amounts of warping were summed up, and the average value was calculated to determine the amount of negative warping. The results are shown in Table 1.

[0169] 3. Discussion Examples 1 to 6, in which the peeling force between the temporary support and the cured resin layer is smaller than the peeling force between the carrier film and the temporary support, are excellent in peelability. That is, in Examples 1 to 6, the temporary support and the cured resin layer peel before the carrier film and the temporary support peel, so that the carrier film can be removed together with the temporary support. As a result, it is found that the workability is excellent. And, by the above peeling, a conductive film having no substrate (for example, a transparent substrate) but a cured resin layer and a conductive layer can be obtained. Since the obtained conductive film does not have a substrate, it is thin and has excellent bending resistance.

[0170] On the other hand, in Comparative Example 1 and Comparative Example 2, in which the peeling force between the temporary support and the cured resin layer is greater than the peeling force between the carrier film and the temporary support, the peelability is reduced. That is, in Comparative Example 1 and Comparative Example 2, the carrier film and the temporary support are peeled off before the temporary support and the cured resin layer are peeled off. As a result, the temporary support cannot be removed together with the carrier film (the temporary support and the carrier film cannot be peeled off at the same time). As a result, the workability is reduced.

[0171] [Table 1] [Explanation of symbols]

[0172] 1 Conductive film transfer material with carrier film 2 Temporary support 3 Cured resin layer 4 Conductive layer 10 Conductive film 20 Career Film

Claims

1. A carrier film, a temporary support, a cured resin layer, and a conductive layer are provided in this order toward one side in a thickness direction, the temporary support and the cured resin layer are peelable from each other, a peel strength between the temporary support and the cured resin layer is smaller than a peel strength between the carrier film and the temporary support, The thickness of the cured resin layer is 7 μm or less, The conductive film transfer material with a carrier film, wherein the conductive layer has a thickness of 150 nm or less.

2. The conductive film transfer material with a carrier film according to claim 1 , wherein a peel strength between the temporary support and the cured resin layer is 1.0 N / 24 mm or less.

3. 3. The conductive film transfer material with a carrier film according to claim 1, wherein the amount of warping measured by the following test is −10 mm or more and 10 mm or less. Test: (1) The conductive film transfer material with the carrier film is cut into a square of 100 mm x 100 mm. (2) The cut conductive film transfer material with the carrier film is heated at 140° C. for 90 minutes. (3) The cut conductive film transfer material with carrier film is placed on a horizontal table with the conductive layer facing up, and the vertical height from the horizontal table is measured at each of the four corners to obtain the amount of warping. (4) The obtained amounts of warping are totaled, the average value is calculated, and this is regarded as the amount of positive warping. (5) If the amount of positive warping is 0 mm or less, the cut conductive film transfer material with carrier film is placed on a horizontal table with the carrier film facing up, and the vertical height from the horizontal table at each of the four corners is measured to determine the amount of warping. (6) The measured warpage amounts are totaled, and the average value is calculated and regarded as the negative warpage amount.

4. A method for producing the conductive film transfer material with a carrier film according to any one of claims 1 to 3, comprising the steps of: A preparation step of preparing a temporary support; a cured resin layer disposing step of disposing a cured resin layer on one surface in a thickness direction of the temporary support; a film forming step of forming a conductive layer on one surface in a thickness direction of the cured resin layer; A method for producing a conductive film transfer material with a carrier film, comprising: a carrier film disposing step of disposing a carrier film on the other surface in the thickness direction of the temporary support.

5. The method for producing a conductive film transfer material with a carrier film according to claim 4 , further comprising the step of: carrying out a carrier film arrangement step after the film formation step.

Citation Information

Patent Citations

  • Transparent electroconductive film laminate and method for processing same

    EP3988299A1

  • Conductive film for transfer and object with transparent conductive layer using this film

    JP2007253425A

  • Conductive film for thermal transfer

    JP2019031040A

  • Conductive film for transfer

    JP2019031041A

  • Transparent conductive film laminate

    JP2020108941A